Comparison of Outcomes of Classical Lichtenstein and Modified Lichtenstein in Patients with Indirect Inguinal Hernia - Ghulam Fatima Komal Memon; Shahid Hussain Mirani; Sadia Saher Memon; Dharmoon Arija; Halar Habibullah; Meena Sadaf (Journal of the Dow University of Health Sciences)
Objective: This study aimed to compare the outcomes of classical Lichtenstein and modified Lichtenstein techniques in patients with indirect inguinal hernia. Methods: This prospective cross-sectional study was conducted at the Department of Surgery, Ghulam Muhammad Mahar Medical College, from September 2024 to February 2025. Patients aged 18–70 years (American Society of Anesthesiologists class I–III) undergoing surgery for indirect inguinal hernia were included and equally divided into classical and modified Lichtenstein repair groups. Baseline characteristics including age, gender, residence, body mass index, diabetes, hypertension, and smoking status were recorded. Primary outcomes included operative time (minutes), postoperative pain score, surgical site infection, and hospital stay duration (days). Results: Of the total 68 patients included, the median age was 47.0 years (40.2–54.0). There were 26 (38.2%) males and 42 (61.8%) females. The median duration of the surgical procedure was significantly shorter in the classical group at 38.5 minutes (35.0–41.2) compared to 50.5 minutes (40.7–54.0) in the modified group (p-value <0.001). Postoperative pain scores, assessed using the visual analogue scale, were consistently significantly lower in the modified group across all time points (p-value <0.001). The length of hospital stay was also significantly shorter in the modified group, with a median of 2.0 days (2.0–3.0) compared to 3.0 days (3.0–4.0) in the classical group (p-value =0.016). Conclusion: Although the classical Lichtenstein technique resulted in a shorter operative duration, the modified technique was associated with significantly lower postoperative pain and a shorter hospital stay, indicating improved recovery outcomes.